An Inquiry on Muslim-Christian Relations in the Qur’ān - Hadiye Ünsal (Umde Dini Tetkikler Dergisi, 2020)
In the Qurʾān, Christians are generally referred as the “Peopleof the Book” in the meaning of those who believe in a divine book,and as “Nasārā” in particular. In the verses referring to Christianity,the good news about the birth of Jesus, his coming into the world andhis miracles are mentioned. Another view in the Qurʾān with respectto Christianity is the rejection of Jesus’ divinity. As such, in many verses,Christian belief of trinity is criticized; it is stated that God will nothave children, that Jesus is human and he is the servant and messengerof God. On the other hand, there are also Qur’anic verses whichpraise some amongst the Christians. In this paper, the process analysisin the Qur’anic verses related to Christianity will be made within theframework of Meccan and Madinan periods that are crucial in termsof tracking the developments in the revelation process of the Qurʾān.Besides that, the question of whether the Qurʾān sees Christians as the“other” during its 23-year revelation period will be discussed. In additionto this, this study will give information about Christianity in thecontext of the Qur’anic revelation. It will also look into the questionof which Christian sect/school corresponds to the Christianity in theArabian Peninsula. However, the nature of miracles attributed to Jesuswill not be mentioned.